Mental Health Pathways Linking Childhood Maltreatment to Interpersonal Revictimization During Adolescence for Girls in the Child Welfare System. Issue 7 (April 2018) - Auslander, Wendy; Tlapek, Sarah Myers; Threlfall, Jennifer; Edmond, Tonya; Dunn, Jerry
This study compares the association of histories of childhood emotional, physical, and sexual abuse, and physical neglect with revictimization among adolescent girls, and investigates the role of posttraumatic stress and symptoms of depression as mediators. Participants were 234 girls aged 12 to 19 years, who have been involved with the child welfare system in a Midwestern urban area. Data were collected from baseline surveys of a trauma-focused group program to which the participants were referred. The majority of participants were youths of color (75%) who were primarily African American (70%), and the remaining participants were White, non-Hispanic (25%). Data were collected through surveys that assessed histories of child abuse and neglect, symptoms of posttraumatic stress and depression, and experiences of physical, verbal, and relational revictimization in the last 3 months. All types of abuse and neglect were significantly associated with higher frequencies of revictimization and higher levels of posttraumatic stress and depressive symptoms. Parallel mediation analyses demonstrated that both posttraumatic stress and depression fully mediated the relationships between emotional abuse and revictimization, and sexual abuse and revictimization. Physical abuse was fully mediated by posttraumatic stress, but not by depression. Results also indicated that neither posttraumatic stress nor depression were mediators for the relationship between neglect and revictimization. There were similar pathways to revictimization in adolescents from emotional and sexual abuse through posttraumatic stress and depression. Evidence is mounting for the deleterious effects of emotional abuse. There is evidence that treatment of both posttraumatic stress and depression in emotionally and sexually abused adolescents involved in child welfare is warranted to prevent future revictimization.